A autoconfrontação em cena: uma investigação sobre o uso de filmes na licenciatura de língua inglesa - Leal, José Luciano Marculino (2017)
The present master‟s thesis, situated in the field of Applied Linguistics, aims to investigate the interpreted work of teachers trainers of an English Language undergraduate course from their reconfigurations about their own work concerning the usage of the textual genre movie in the classroom. In order to achieve this aim, we based our studies on the Sociodiscursive Interactionism theoretical framework (BRONCKART, 2008, 2006, 1999; MACHADO, 2009; CRISTOVÃO, 2008) and on the Labor Sciences (CLOT, 2012, 2010, 2007; FAÏTA, 2002). Thus, we start from the following research questions: i) what are the main themes represented in the self-confrontation interviews and what do they reveal with respect to the process of English language pre-service teacher education? ii) how do the teachers trainers evaluate their own work with the genre movie and what are the implications for language teaching? Based on these research questions, we have established, respectively, the following specific objectives: i) to identify the most significant thematic contents in the language action of teachers trainers in the self-confrontation interviews, and to investigate what they reveal about the teaching work in language teaching; ii) to analyze the enunciative mechanisms and the constitutive elements of teaching work conveyed by the teachers trainers, discussing the implications for the pre-service teacher education. Regarding the methodological features, the research, with a qualitative interpretative basis of an exploratory nature, was developed through the methodology of self-confrontation with three teachers trainers of the English Language undergraduate course at the State University of Paraíba, Campus I - in the city of Campina Grande, in the first semester of 2016, as a means to investigate the interpretation of their own language action with respect to the didactic-pedagogical usage of movies. In addition to the self-confrontation interviews, we applied questionnaires in order to know the experiences, the practices and the relationship of the participants with movies in different domains of their lives. Regarding the results, the most recurring identified themes, based on our analytical reading, allowed us to perceive that the teachers trainers directed their analysis in evaluations about themselves and evaluations about their own work with the movies in the classroom due to their own objects of study. On one hand, in the evaluative positions on themselves, it was highlighted the reflections regarding the movement and posture in the classroom, which allowed the participants to see themselves as spectators of themselves in action. On the other hand, the evaluations of teachers trainers about their own work with film texts have brought to light: previous experiences, socio-subjective conceptions related to the genre movie, as well as issues about the singularities of films‟ narrative, besides the discussions about its relevance and didactic effectiveness. From the perspective of implications, the realization of this research has brought concerns which reinforce the necessity of thinking specifically the movie as an object of teaching; furthermore, we believe in the relevance of teachers trainers to promote a greater specification/orientation of the activities related to the use of films in pre-service teacher education contexts. Therefore, this research provided, in general, the possibility for the teachers involved to relive the movements employed in the use of movies in the classes highlighted and to reflect on these situated movements.